Challenges in developing and implementing institutional repositories in higher educational institutions - Abd Aziz, Muhamad Faizal (Persatuan Pustakawan Malaysia, 2011)
Institutional repositories have become popular amongst higher educational institutions around the world. Many higher educational institutions, especially universities, have developed institutional repositories as the alternative medium for their scholars to deposit copies of their works. Establishing an institutional repository enables a university to publicise its research and teaching programmes by enabling access to the work of its staff and students. The academic work of an institution can be presented in one place rather than just spread amongst hundreds of journals, thus increasing visibility and prestige. However, there are several obstacles which can become a challenge in developing Irs and has to be overcome.